Coefficient of Efficiency in Pedagogical and Scientific Work of a Teacher and a Group of University Teachers - Mamrilla, Dusan; Kravcakova, Gabriela (Communications - Scientific letters of the University of Zilina, 2012)
Financial resources are provided for realization of pedagogical performance (PP) and scientific performance (SP) at the university. Efficiency of its usage is subject of research for many researchers. In this paper we show practical quantification model of PP and SP of university teacher and university organizational units (i.e. groups of teachers, university department, groups of departments, faculty, groups of faculties, university). We respect recommended expenditure ratio PP : SP 60 : 40 of provided financial resources.